1999
DOI: 10.1073/pnas.96.9.5173
|View full text |Cite
|
Sign up to set email alerts
|

Association of a missense change in the D2 dopamine receptor with myoclonus dystonia

Abstract: Hereditary autosomal dominant myoclonus dystonia (MD) is a movement disorder characterized by involuntary lightning jerks and dystonic movements and postures alleviated by alcohol. Although various large families with MD have been described, no positive linkage has been found to a chromosomal location. We report a family with eight members with MD. Linkage analysis identified a 23-centimorgan region on chromosome 11q23 that cosegregates with the disease state (maximum multipoint logarithm of odds score ‫؍‬ 2.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0
3

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(73 citation statements)
references
References 36 publications
3
65
0
3
Order By: Relevance
“…Positronemission tomography (PET) studies in Lesch-Nyhan disease show reductions in [ 18 F]-DOPA uptake, and in labeling with WIN-35,428, a marker of dopamine transporter, in the basal ganglia and other regions of the brain (Ernst et al, 1996;Wong et al, 1996). Mutations in the gene that codes for the rate-limiting enzyme in dopamine metabolism, tyrosine hydroxylase, also give rise to dystonias (Knappskog et al, 1995), as do mutations within the dopamine D2 receptor gene (myoclonus-dystonia, DYT11, Klein et al, 1999), or polymorphisms within the dopamine D5 receptor gene (Placzek et al, 2001). …”
Section: The Role Of Dopamine In Dystoniamentioning
confidence: 99%
“…Positronemission tomography (PET) studies in Lesch-Nyhan disease show reductions in [ 18 F]-DOPA uptake, and in labeling with WIN-35,428, a marker of dopamine transporter, in the basal ganglia and other regions of the brain (Ernst et al, 1996;Wong et al, 1996). Mutations in the gene that codes for the rate-limiting enzyme in dopamine metabolism, tyrosine hydroxylase, also give rise to dystonias (Knappskog et al, 1995), as do mutations within the dopamine D2 receptor gene (myoclonus-dystonia, DYT11, Klein et al, 1999), or polymorphisms within the dopamine D5 receptor gene (Placzek et al, 2001). …”
Section: The Role Of Dopamine In Dystoniamentioning
confidence: 99%
“…For instance, mutations in two important genes in the biosynthesis of dopamine; the GTP cyclohydrolase (8)(9)(10) and tyrosine hydroxylase genes (11)(12), were found in patients with doparesponsive dystonia. Similarly, a mutation in the dopamine D2 receptor (D2DAR) was associated with myoclonus dystonia (13). Consistent with a potential role for the dopamine system in dystonia, the torsinA gene is expressed at high levels in dopamine neurons of the substantia nigra (14)(15)(16).…”
mentioning
confidence: 96%
“…Because new results have revealed that SSTR5 and DRD2 form functional heterodimers [Rocheville et al, 2000], we also checked the Danish and French cases for the following five mutations in the DRD2 gene: Val96Ala [Gejman et al, 1994], Val154Ile [Klein et al, 1999], Pro310Ser [Gejman et al, 1994], Ser311Cys [Itokawa et al, 1993], and Thr351Ala (available via the NCBI SNP database (http://www.ncbi.nlm.nih.gov/SNP/), SNP ID rs1110977ref). Not surprisingly, we were unable to find any of the five DRD2 missense mutations among cases since they are all very rare.…”
Section: Discussionmentioning
confidence: 99%